Edukasi Terapi Relaksasi Genggam Jari dan Relaksasi Nafas Dalam terhadap Penurunan Tekanan Darah pada Penderita Hipertensi Primer di Gampong Meunasah Meucap Kecamatan Peusangan - Al Ridha, Muttaqin; Munawwarah, Khairiyatul; Habibi, Habibi (Penerbit Goodwood, 2023)
Purpose: The purpose of this service is to teach the public about relaxing the finger grip on lowering blood pressure in sufferers. Method: The method used in this service is a method of mentoring and educating the community about finger grip relaxation therapy and deep breathing. This service was carried out in Gampong Meunasah Mekata, Peusangan District, Bireuen Regency. Result: Hypertension in the world based on the World Health Organization (WHO) in 2012 showed that around 982 million people or 26.4% of the world's inhabitants suffer from hypertension with a ratio of 26.6% men and 26.1% women. This figure is likely to increase to 29.2% in 2025. The prevalence of hypertension in Indonesia in 2018 is based on measurement results in people aged ?18 years of 34.1%, the highest in South Kalimantan is 44.1% while the lowest is in Papua with 22. 2%.